2014
DOI: 10.1128/jvi.00591-14
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Probes Targeting the Viral PPxY-Host Nedd4 Interface Block Egress of a Broad Range of RNA Viruses

Abstract: Budding of filoviruses, arenaviruses, and rhabdoviruses is facilitated by subversion of host proteins, such as Nedd4 E3 ubiquitin ligase, by viral PPxY late (L) budding domains expressed within the matrix proteins of these RNA viruses. As L domains are important for budding and are highly conserved in a wide array of RNA viruses, they represent potential broad-spectrum targets for the development of antiviral drugs. To identify potential competitive blockers, we used the known Nedd4 WW domain-PPxY interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 87 publications
6
88
0
Order By: Relevance
“…Overall, the inhibition of M protein function by both AP3B1-derived polypeptides and overexpressed full-length AP3B1 supports the general concept that binding interfaces between host factors and buddingrelevant viral proteins can be targeted for disruption as an effective antiviral approach (47,57). Indeed, small-molecule budding inhibitors have recently been identified that target the PTAP-Tsg101 interface in the case of HIV-1 (58,59) or the PPxY-Nedd4 interface in the cases of Ebola virus, Marburg virus, Lassa virus, and rabies virus (60). Similar approaches that target the AP3B1-M binding interface may prove useful in the identification of new therapeutics for paramyxovirus infections.…”
Section: Discussionmentioning
confidence: 82%
“…Overall, the inhibition of M protein function by both AP3B1-derived polypeptides and overexpressed full-length AP3B1 supports the general concept that binding interfaces between host factors and buddingrelevant viral proteins can be targeted for disruption as an effective antiviral approach (47,57). Indeed, small-molecule budding inhibitors have recently been identified that target the PTAP-Tsg101 interface in the case of HIV-1 (58,59) or the PPxY-Nedd4 interface in the cases of Ebola virus, Marburg virus, Lassa virus, and rabies virus (60). Similar approaches that target the AP3B1-M binding interface may prove useful in the identification of new therapeutics for paramyxovirus infections.…”
Section: Discussionmentioning
confidence: 82%
“…As with our other tuberculosis-focused research 32, 33 , and computational approaches to repositioning compounds 34 we embrace the essentiality for computational predictions to be interrogated through rigorous experimental studies. For example at least two in silico docking studies screened commercially available compounds 14, 15 . We propose that docking FDA approved drugs could also be a viable first step to identifying potential compounds that could be used.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified non-FDA approved drugs including an in silico docking approach to identify molecules targeting the viral Nedd4-PPxY interface 14 . These molecules were similar to the FDA benzimidazole and aminoquinoline 8, 9 compounds that were active against EBOV.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that several small molecules that interfere with the late domain-mediated interactions between VP40 and host factors efficiently inhibit replication of a broad range of RNA viruses, including filoviruses in vitro [93,94]. Importantly, one of these molecules protected mice from lethal ebolavirus challenge [93].…”
Section: Assembly/egressmentioning
confidence: 99%